1991
DOI: 10.1007/bf02050063
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparative study of magnetic resonance imaging versus transrectal ultrasound for preoperative staging and follow-up of rectal cancer

Abstract: The efficiency of magnetic resonance imaging (MRI) and that of transrectal ultrasound (TRUS) were compared in preoperative staging of 15 patients with rectal cancer and in postoperative follow-up of 12 patients. Thirteen of the 15 patients evaluated for preoperative staging were operated on. Preoperative staging and pathologic finding were identical in 11 patients (84.6 percent) examined by TRUS and in 10 patients (76.9 percent) examined by MRI. Recurrent cancer was detected in 3 of 12 patients in the follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…In addition, CT scanning is not accurate in assessing the depth of wall penetration in the rectum and appears to lack an ability to detect pelvic lymph nodes. TRUS is a new diagnostic modality that has become useful in aiding the surgeon in selecting the appropriate therapy for rectal cancer because of its high accuracy in determining the depth of invasion of the rectal cancer and the presence or absence of metastatic lymph nodes preoperatively [1,3]. When the accuracy of ultrasonographically is determined, the depth of invasion is compared with the histologic results; accuracy rates in the 90 % range have been documented by many authors [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, CT scanning is not accurate in assessing the depth of wall penetration in the rectum and appears to lack an ability to detect pelvic lymph nodes. TRUS is a new diagnostic modality that has become useful in aiding the surgeon in selecting the appropriate therapy for rectal cancer because of its high accuracy in determining the depth of invasion of the rectal cancer and the presence or absence of metastatic lymph nodes preoperatively [1,3]. When the accuracy of ultrasonographically is determined, the depth of invasion is compared with the histologic results; accuracy rates in the 90 % range have been documented by many authors [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…When the accuracy of ultrasonographically is determined, the depth of invasion is compared with the histologic results; accuracy rates in the 90 % range have been documented by many authors [4,5]. Some studies have shown the superiority of transrectal ultrasonography compared to CT scanning, but others have shown little difference [3,7]. Even though overall accuracy rates are strongly dependent on the investigator's experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La resonancia magn茅tica de pelvis presenta resultados similares a la ER en la etapificaci贸n del c谩ncer de recto 20,21 , en particular con el uso de la bobina endorectal 22,23 . Sin embargo en lesiones tumorales tempranas, la ER mantiene una ventaja respecto a la resonancia 24 .…”
Section: Discussionunclassified
“…This in part depends on the MRI technique, whether a surface (phasedarray) or an endo-rectal coil is used and is operator dependent. Satoh [21] found TRUS more accurate than MRI, while Thaler [22] and Waizer [23] found no difference between the two. In two recent prospective comparative studies there was no significant difference between TRUS and endo-rectal MRI in both T and N [24] ( Tables 2 and 3).…”
Section: Trans-rectal Ultrasound and Magnetic Resonance Imagingmentioning
confidence: 99%